Application of circadian rhythm in osteoporosis prevention and treatment: from light, diet, and exercise to chronotherapy - Qian, Jun; Huang, Kai; Zhai, Qiaocheng (Frontiers in Endocrinology, 2025)
Osteoporosis is a prevalent systemic bone disorder characterized by reduced bone mass, deterioration of bone microstructure, and increased bone fragility, significantly compromising the quality of life, particularly among elderly and postmenopausal populations. The circadian clock serves as a critical physiological mechanism for maintaining homeostasis and regulating rhythmic biological processes, playing an essential role in bone metabolism regulation. Recent studies have revealed strong associations between circadian disruption and the development and progression of osteoporosis, providing novel perspectives for intervention strategies. This comprehensive review examines the role of the circadian clock in osteoporosis and explores the current applications and future prospects of circadian-based interventions, including light exposure, dietary modifications, physical activity, and chronotherapy, in osteoporosis management. The objective is to offer comprehensive and precise strategic insights for osteoporosis prevention and treatment.